Assessment of wildlife-induced crop damage and farmer coping strategies in Mbire district, Zimbabwe - Dzuda, Blessing; Falconnier, Gatien; Chimonyo, Vimbayi Grace Petrova; Chimimba, Edmore; Chimusimbe, Edwin (CGIAR, 2025)
Human–wildlife conflict remains one of the most pressing challenges for farming communities living alongside protected areas in Zimbabwe. In Mbire District, crop raiding by megafauna continues to threaten food security, household livelihoods, and the overall resilience of smallholder farming systems. To better understand the scale of these impacts, we conducted a field-based assessment during the 2024/25 agricultural season, directly measuring crop damage across selected farms and documenting the strategies farmers use to cope with wildlife incursions. This report presents the findings from that work, highlighting the extent and severity of crop damage, the effectiveness of the various deterrent practices used by farmers and other aspects of wildlife-induced damages. 118 farmers were surveyed from both wards 2 and 3 of the Mbire district, and about 80.2 ha (30.8ha Ward 2 and 49.4ha Ward 3) of farm crop land was covered. Analysis of the collected data showed that overall, the field area damaged by wildlife was small (2.1%). Farmers in Ward , closer to the conservation areas, experienced more crop damage, with 1.5% of the surveyed cropland with observed damage, whilst in ward 3, 0.6% damage of the surveyed cropland had observed damage. Species with high severity of crop damage were elephants and monkeys. In Ward 2, both animals dominated most of the field attacks, while in Ward 3, monkeys were the only animal invading the fields. Bush pigs are also among the field invasive species, but the severity of field damage was lower compared to elephants and monkeys. Out of 118, 95 farmers across all wards have employed different coping strategies in trying to mitigate the incidence and severity of attack on their field crops, with a mean of 2.02 practices per farmer. Farmers reported varying levels of perceived effectiveness across the different deterrent strategies. Chilli-based methods received the highest effectiveness ratings, with an average score of 4.35 out of 5, although these ratings came from a relatively small number of fields (17) in which they are being used. Other Methods, which was a mix of additional deterrent practices were also rated moderately high, with a mean of 3.79 based on 38 fields in which they are being used. The use of fire had a slightly lower mean rating of 3.58 from 60 fields, while barriers and fencing received the lowest effectiveness rating, averaging 3.32 from 50 fields they are implemented. With this information at hand, it can be concluded that overall incidence of damage was rather low (<5% of the surveyed area), and in the vast majority of fields (128/168 = 76%), farmer implemented at least two deterrent methods. These findings altogether indicate that possibly incidence of damage is low, thanks to substantial labour investment by farmers in preventing these. In addition to field-level crop losses, households also reported wildlife-related damage to granaries. The assessment showed that granary raiding was present in both wards, with Ward 2 recording 11 households affected out of approximately 33 surveyed, while Ward 3 had 22 affected households out of about 85 surveyed. The stacked distribution of affected and unaffected households indicates that although Ward 2 had fewer total households, a notable share still experienced granary attacks, whereas Ward 3, with a larger surveyed population, had a higher number of households reporting raided granaries. These results complement the field damage findings by showing that wildlife incursions extend beyond croplands to stored grain, affecting households differently across wards. The livestock assessment showed that wildlife attacks affected several animal types across both wards, with goats and poultry experiencing the highest levels of incidents. In Ward 2, goats displayed the widest spread of reported attacks, while poultry also showed moderate losses, whereas sheep and cattle recorded comparatively low attack levels. A similar pattern was observed in Wad 3, where goats and poultry again had higher average attack numbers, including a few farmers reporting notably larger losses, while sheep and cattle remained the least affected. Complementing these findings, the identification of the most frequent livestock predators showed that hyenas were the dominant predators in both wards, accounting for nearly all reported incidents. Small numbers of attacks involving baboons/monkeys, mixed hyena–baboon events, and isolated lion cases were also recorded, though these were far fewer. Together, these results indicate that livestock predation is concentrated mainly on goats and poultry, with hyenas responsible for the majority of attacks across both wards. Reports of human–wildlife encounters revealed a clear contrast between the two wards, with Ward 2 experiencing both a higher frequency of dangerous wildlife and the most severe human injuries. Households in Ward 2 identified elephants as the primary human-attacking animal, followed by buffalo and monkeys/baboons, indicating a broader range of threatening wildlife in this area. In Ward 3, however, the pattern is more concentrated, with attacks attributed mainly to buffalo and wild pigs, and no reports of elephants or primates. Ward 2 recorded severe injuries and a few deaths, alongside minor injuries, whereas Ward 3 reported only minor injuries among a very small share of residents. While human attacks were relatively uncommon overall, Ward 2 carried both the greatest diversity of aggressive wildlife and the full burden of severe incidents.